Dosing Variation at Initiation of Adalimumab and Etanercept and Clinical Outcomes in Juvenile Idiopathic Arthritis: A Childhood Arthritis and Rheumatology Research Alliance Registry Study. Issue 2 (11th November 2022) - Verstegen, Ruud H. J.; Shrader, Peter; Balevic, Stephen J.; Beukelman, Timothy; Correll, Colleen; Dennos, Anne; Phillips, Thomas; Feldman, Brian M.; ,
Abstract : Objective: To determine the dose–response relationship of tumor necrosis factor (TNF) inhibition in the treatment of juvenile idiopathic arthritis (JIA). Methods: Participants of the Childhood Arthritis and Rheumatology Research Alliance Registry were eligible for inclusion in the analyses if they started TNF inhibition treatment for JIA. The primary treatment response was determined 3 to 7 months after the start of treatment, based on the JIA American College of Rheumatology Pediatric criteria for improvement, clinical Juvenile Arthritis Disease Activity Score, and persistence of treatment after 6 months. Subsequently, pooled logistic regression models were performed to include long‐term follow‐up data. The models were adjusted for risk factors associated with poor treatment response. Dosing was expressed by body weight, body surface area, ideal body weight, fat free mass, and lean body mass. Results: Participants treated with adalimumab (n = 328) and etanercept (n = 437) were included in the analyses (median dose 0.82 mg/kg body weight [interquartile range (IQR) 0.66–1.04] and 0.83 mg/kg body weight [IQR 0.75–0.95], respectively). The majority of analyses did not show a relationship between dose and outcome. Where associations were found, results were conflicting. Alternative dosing characteristics based on ideal body weight, fat free mass, and lean body mass did not result in stronger or more consistent associations. Conclusion: This study was not able to confirm our hypothesis that increased dosing of TNF inhibitors results in improved treatment outcomes. Although adjustment was performed for risk factors of impaired treatment response, residual confounding by indication likely explains the negative associations found in this study.